Peran Pendidikan Islam Dalam Menanamkan Nilai Akhlakul Karimah Pada Peserta Didik Di Era Globalisasi Di Sd Negeri 18 Kalosi - Asran Asran; Zamri Zamri; Hasmi Hasmi; Hasriyanti Mandalika Hasan; Amaluddin Amaluddin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The era of globalization and the development of digital technology have had a significant impact on the character formation of students, especially in elementary schools. This study aims to analyze the role of Islamic Religious Education (PAI) in instilling noble moral values ​​in students at SD Negeri 18 Kalosi through learning, teacher role models, religious habits, and collaboration between schools, families, and the community. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, semi-structured interviews, and documentation, which were then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results show that Islamic Religious Education has a strategic role as a pillar of student moral formation through the integration of religious values ​​into learning and school activities. Teachers act as role models by displaying behavior in accordance with Islamic teachings, thus becoming moral models for students. School programs such as the Dhuha prayer, Al-Quran recitation, and Friday Blessings provide practical space for students to cultivate noble moral values. However, the biggest challenges arise from the influence of digital media, inconsistent mentoring at home, and limited parental collaboration. This study concludes that sustainable implementation of Islamic Religious Education (PAI), supported by collaboration between families and the community, is essential for maintaining students' character amidst global developments. This research contributes to strengthening the practice of Islamic character education in elementary schools in response to social and cultural changes in the digital era.